THE POWER OF INFLUENCERS: IMPACT ON PURCHASE INTENT THROUGH PARASOCIAL ENGAGEMENT - Mehmet Gökerik (International Journal of Eurasia Social Sciences, 2024)
Today's social media platforms have become indispensable tools for businesses to engage with their target audiences. Social media marketing holds a significant place as a dynamic and effective strategy that enables businesses to interact with their target audiences. This approach allows businesses to communicate directly and personally with consumers while also providing access to wide audiences and high interaction potential. At the heart of this strategy, social media influencers play a crucial role in reliably transmitting businesses' messages to their followers. The strong bonds between influencers and their followers can positively influence consumers' brand perception, loyalty, and intention to purchase. Parasocial interaction theory suggests that media users can develop one-sided relationships with media personalities, and these relationships can influence users' attitudes and behaviors towards businesses or products. The parasocial interactions that develop between social media influencers and their followers have become powerful and effective, especially in the era of social media. This study aims to contribute to consumer behavior, parasocial interaction theory, and marketing practice. The research is a quantitative and descriptive analysis that examines the effect of variables such as influencers' perceived credibility, attitudes towards influencers, and the quality of their posts on purchase intention through parasocial interaction. Data collected through surveys in Karabük were analyzed using SPSS 21 and AMOS 20 statistical analysis programs through structural equation modeling. The results highlight the significant impact of influencer marketing on parasocial interaction and, indirectly, on purchase intention. This analysis demonstrates the potential of influencer marketing within the parasocial interaction theory framework to influence consumers' purchase intentions. The study emphasizes that the impact of influencers cannot be reduced merely to the number of followers or the visual appeal of content; beyond that, the depth and quality of the parasocial relationships established are also crucial.